2015
DOI: 10.1177/0960327115595687
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant, enzyme inhibition, and cytotoxic activity of three anthraquinones (alizarin, purpurin, and quinizarin)

Abstract: Objective: The aim of this work was to investigate the cytotoxic, antioxidative, and enzyme inhibition effects of alizarin, quinizarin, and purpurin, which are anthraquinones (AQ). Methods: Cytotoxic effects were evaluated with cell inhibition rate by 3-(4,5-dimethylthiazol- 2-yl)-2,5-diphenyltetrazolium bromide assay. Different chemical assays, including free radical scavenging activity (1,1-diphenyl-2-pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 41 publications
(57 reference statements)
1
28
0
Order By: Relevance
“…Hence, development of alternative and safer enzyme inhibitory agents is highly recommended. These new natural compounds have shown effective enzyme inhibition without adverse effects …”
Section: Introductionmentioning
confidence: 99%
“…Hence, development of alternative and safer enzyme inhibitory agents is highly recommended. These new natural compounds have shown effective enzyme inhibition without adverse effects …”
Section: Introductionmentioning
confidence: 99%
“…It occurs as a colorless glycoside in the root of the common madder plant ( Rubia tinctorum L.) [ 5 , 6 ]. The cellular and molecular basis for the reported health-promoting properties of purpurin in vitro and in vivo seems to be associated with antioxidative [ 7 ] and antigenotoxic [ 8 , 9 ] effects that include (a) chemoprotective effects against DNA adduct formation in mice; and (b) inhibition of biological alkylations of DNA by carcinogenic heterocyclic amines, present in heat-processed (cooked) meat and poultry products [ 10 , 11 , 12 ]. In the present study, we observed that anti-inflammatory and immunomodulating properties in cells might also contribute to the mentioned beneficial effects.…”
Section: Introductionmentioning
confidence: 99%
“…In a related study, Zengin et al investigated the antioxidative effects of the following three anthraquinones: alizarin, quinizarin, and purpurin [49]. Purpurin showed the highest activity.…”
Section: Anti-oxidative Properties Of Anthraquinonesmentioning
confidence: 99%